Building a Nyoongar work practice model for Aboriginal youth mental health: prioritising trust, culture and spirit, and new ways of working. Issue 2 (4th May 2022) - Culbong, Tiana; Crisp, Nikayla; Biedermann, Britta; Lin, Ashleigh; Pearson, Glenn; Eades, Anne-Marie; Wright, Michael
ABSTRACT: Mainstream youth mental health services struggle to comprehend the connection between colonisation and service provision for Aboriginal young people. This is the consensus agreed by Aboriginal Elders from Perth, Western Australia and young Aboriginal leaders within their communities (Wright, Culbong, Crisp, Biedermann, & Lin (2019). 1–7). What is required is a more nuanced, culturally relevant approach to both an understanding of the impact of colonisation on mental health and help-seeking behaviour if they are to provide equitable access for Aboriginal young people. In this paper, we report on a three-year participatory action research (PAR) project conducted on Whadjuk Nyoongar country in Perth, Western Australia. An innovative model of care framework developed from the project and described in this paper, focuses on key components that both inform and assist service providers in improving service provision to Aboriginal young people. The model, depicted as a tree, symbolises strength and growth, with the 'roots' of the tree, holding trust, culture and spirit. This paper details a culturally-safe co-design process that was held and directed with Elders, in partnership with young people, youth mental health service staff and youth policy staff.